Preserving the Viability of Local Products from BUMDes Pondok Kelor Through Digital Marketing - Tutik Handayani; Rizki Febri Eka Pradani (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze digital marketing strategies for maintaining the market presence of local products from BUMDes Pondok Kelor, specifically Jamu Pelka Duk Kelor. In this study, the market presence of local products is defined as the products’ ability to maintain brand visibility, ensure marketing sustainability, and remain in the market. Research Method: This study employed a qualitative descriptive case study design. Data were collected through observation, semi-structured interviews, and documentation, and then analyzed using data reduction, data presentation, and triangulation to draw conclusions. Results and Discussion: The research findings indicate that BUMDes Pondok Kelor utilizes Instagram, TikTok, WhatsApp, Shopee, and government platforms such as e-Katalog, Bela-Beli, and SI MADU to expand product visibility and market access. However, the effectiveness of these strategies remains limited by managers’ lack of digital literacy, production capacity, and raw material availability, resulting in suboptimal implementation of digital marketing. Implications: The research findings underscore the importance of strengthening digital competencies, increasing production capacity, and integrating social media and government platforms to support the sustainability of BUMDes local products. Originality: This study shows that the success of digital marketing at BUMDes is determined not only by the use of digital media but also by the organization’s readiness to integrate human resource capacity, business operations, and support from the government’s digital ecosystem.